2007
DOI: 10.3382/japr.2006-00121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chilling Method and Deboning Time on Broiler Breast Fillet Quality

Abstract: A study was conducted to determine the effects of chilling method and postmortem aging time on broiler breast fillet quality. One hundred fifty eviscerated broiler carcasses were removed from a commercial processing line before chilling and transported to the laboratory. Half of the carcasses were chilled by dry air, whereas the other half were chilled by water immersion. Immersion-chilled (IC) carcasses were divided into 3 groups (0, 1.67, and 24 h) based on postchill fillet aging time on the carcass. Air-chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
1
13
1
Order By: Relevance
“…There were no differences in color and pH between AC and IC samples. These results are consistent with reported observations of the changes in pH (decreased) and lightness (increased) of chicken breast fillets with aging time (Lyon et al, 1985;Young et al, 1999;Cavitt et al, 2005) and also agree with previous studies that showed no significant differences between AC and IC for pH, L*, a*, and b* values of raw breast fillets deboned at the same postmortem time (Fleming et al, 1991;Huezo et al, 2007b). Table 3 shows ANOVA and average intensity scores for 12 texture and 9 flavor sensory attributes of the cooked breast meat, fillets, and tenders.…”
Section: Carcass Time-temperature Profiles Carcass Weight and Fillesupporting
confidence: 95%
See 2 more Smart Citations
“…There were no differences in color and pH between AC and IC samples. These results are consistent with reported observations of the changes in pH (decreased) and lightness (increased) of chicken breast fillets with aging time (Lyon et al, 1985;Young et al, 1999;Cavitt et al, 2005) and also agree with previous studies that showed no significant differences between AC and IC for pH, L*, a*, and b* values of raw breast fillets deboned at the same postmortem time (Fleming et al, 1991;Huezo et al, 2007b). Table 3 shows ANOVA and average intensity scores for 12 texture and 9 flavor sensory attributes of the cooked breast meat, fillets, and tenders.…”
Section: Carcass Time-temperature Profiles Carcass Weight and Fillesupporting
confidence: 95%
“…Therefore, it is impossible to conclude if AC has any advantage over IC on improvement of texture quality of chicken breast meat based on these results. In 2007, Huezo et al (2007b) made the side-by-side comparison of the effects of AC and IC methods on broiler breast fillet quality. However, in their experiments, sensory quality of treated fillets was not measured and the fillets were deboned at either 2.5 or 24 h after the initiation of chilling.…”
Section: Sensory Descriptive Profiles Of Chicken Pectoralis Major Andmentioning
confidence: 99%
See 1 more Smart Citation
“…But Huezo et al [15] determined that L*, a*and b* values as 61.4, 1.5 and 1.0 for broiler carcass were removed from a commercial slaughter house after 24 h storage. The results obtained herein deal with skin color showed that a* values were lower at SG according to FG (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is observed that darker broiler meat is associated with lower muscle ultimate pH (pHU or pH24); pHU is measured at 24 h after killing. It has been demonstrated that there is a high correlation between breast muscle ultimate pH and L* value [11,[14][15][16][17][18] . As pH increases, the L* value decreases; a high-pH of muscles, therefore, has darker color than those of low-pH.…”
Section: Introductionmentioning
confidence: 99%